Evaluating The Role Of Latch Scoring Tool In Identifying And Correcting Breastfeeding Problems - Verma, Sanjana; Srivastava, Anshuman (Journal of Neonatal Surgery, 2025)
Introduction: Breastfeeding is critical for neonatal nutrition and immunity, yet many mothers face early breastfeeding challenges that can undermine exclusive breastfeeding rates. The LATCH scoring tool offers a structured method to identify and address these challenges by assessing five essential components of breastfeeding effectiveness. Methodology: A prospective observational study was conducted over 15–18 months at tertiary care hospital in Pilkhuwa, Hapur, involving 170 stable mother– neonate dyads (≥34 weeks gestation, birth weight >1.8 kg). Each dyad was assessed on Day 1 and Day 2 postpartum using the LATCH scoring system (range: 0–10). Mothers with lower scores received one-on-one counselling focused on proper positioning, latch techniques, and comfort measures. Data was recorded in a structured format and analysed using descriptive and inferential statistics (p < 0.05 considered significant). Results: On Day 1, 57.1% of dyads scored 5–7, while 32.3% scored 8–10, with a mean LATCH score of 7.07. Following counselling, 81.2% scored between 8–10 on Day 2 (mean 8.69), reflecting a statistically significant improvement (p < 0.001). Improvement in LATCH score was observed following counselling. Higher LATCH scores on Day 2 were strongly linked to successful exclusive breastfeeding at discharge and those neonates with lower initial LATCH score had higher chances of developing neonatal complications. Conclusion: The LATCH scoring tool effectively identifies and corrects breastfeeding difficulties when coupled with focused counselling. Integrating routine LATCH assessments into postpartum care can enhance exclusive breastfeeding rates and promote better neonatal health outcomes.